A review of reindeer (Rangifer tarandus tarandus) disturbance research in Northern Europe: towards a social-ecological framework?. (17th November 2022) - Gundersen, Vegard; Myrvold, Knut Marius; Kaltenborn, Bjørn Petter; Strand, Olav; Kofinas, Gary
Abstract: Disturbance of wild reindeer from human activity is a key challenge for wildlife management. We reviewed recent literature on reindeer disturbance in Northern Europe and discuss a major lacuna in this field of research, namely knowledge about the complexity of human behaviour, which is the major agent of disturbance. Past studies have rarely included detailed data on human activities, but instead treated fixed infrastructure as valid proxies for human presence. However, ignoring the dynamic and flexible nature of human agency as a driver of disturbance may bias our interpretation of the observed responses. We argue that incorporating information about the spatiotemporal patterns of human use of infrastructure and the characteristics of the users may greatly improve our knowledge of the potential impacts on wild and semi-domestic reindeer populations and contribute to improved management of their ranges.